Aryl hydrocarbon receptor‐based bioassays for dioxin detection: Thinking outside the box. Issue 4 (26th December 2017) - Otarola, Gaston; Castillo, Hector; Marcellini, Sylvain
Abstract: Despite intensive media coverage and international regulations, man‐made persistent organic pollutants such as dioxins represent a serious environmental and health threat. Their detection by sophisticated chromatography technologies is highly complex, impeding the constant monitoring of food or environmental samples. This limitation has fostered the development of generations of bioassays exploiting the molecular function of the aryl hydrocarbon receptor (AhR), which binds toxic compounds and directly activates the transcription of target genes. Here, we review the rich panel of available AhR‐dependent bioassays and propose a novel classification based on the source of AhR, which can either be endogenously produced by cell types or tissues naturally responsive to dioxins, or exogenously introduced into a wide range of cellular contexts. In both cases, in vitro and in vivo strategies have been engineered to monitor the formation of molecular complexes, and the activation of direct downstream targets or reporter genes. We evaluate and compare bioassays based on exogenous and endogenous AhR proteins and discuss their specific challenges, strengths and opportunities for futures applications. Undoubtedly, the dynamic field of AhR‐dependent bioassays will keep providing new and original strategies to help protect human health and ecosystems from persistent organic pollutants. Abstract : Persistent organic pollutants represent a serious threat to human health and have driven the rapid diversification of AhR‐based bioassays. Here, we propose a novel classification for such bioassays by emphasizing the importance of the AhR source. Indeed, the AhR protein can either be produced to high levels by a tissue or cell line of interest (endogenous origin), or genetically introduced in a foreign cell context (exogenous origin). Both strategies are compared and their possible limitations, challenges and opportunities are discussed.